Running and Clicking: Future Narratives in Film - Schenk, Sabine (De Gruyter, 2013)
Running and Clicking examines how Future Narratives push against the confines of their medium: Studying Future Narratives in movies, interactive films, and other electronic media that allow for nodes, this volume demonstrates how the dividing line between film and game is progressively dissolved. Focused on traditional mass media, transitional media, and new media, it also touches on transmedial storytelling and virtual reality, discussions of the political power of the imaginary and of the possible fate of Future Narratives in the post-human hegemony of the simulated real.